ANALISIS PERSPEKTIF MAHASISWA SISTEM INFORMASI ITS TERHADAP KURIKULUM MERDEKA BELAJAR KAMPUS MERDEKA - Rahmah Fauzia; Muhammad Ali Fikri (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Palangka Raya, 2023)
Universities are required to be able to adapt the existing education system to the current state of the Indonesian industry. Merdeka Belajar Kampus Merdeka (MBKM) is a policy of the Minister of Education and Culture that encourages students to master various sciences as a subject before entering the world of business and industry. The purpose of the study was to find out the perspectives of the ITS Information Systems Department students regarding the implementation of the MBKM policy. This research uses a case study method with a qualitative approach. The results showed that 42.1% of students contributed to discussions/meetings/workshops related to the preparation for the implementation of MBKM, 44.7% of students stated that there was a fairly good increase in capacity, and 50% of students stated that there was an improvement in the quality of the learning process well. The main obstacle that affect the implementation of MBKM is curriculum adjustments.